Ответ:
Объяснение:
x (x + 1 ) (x + 2) (x + 3) = 48
(x² + x) (x + 2) (x + 3) = 48
(x³ + 2x² +x² + 2x) (x + 3) = 48
x⁴ + 3x³ + 3x³ + 9x² +2x² + 6x = 48
x⁴ + 6x³ + 11x² + 6x = 48
x⁴ + 6x³ + 11x² + 6x - 48 = 0
x⁴ + 3x³ + 3x³ - 6x² + 9x² + 8x² - 18x + 24x - 48 = 0
(x² + 3x - 6)*(x² + 3x + 8) =0
x² + 3x - 6 = 0
x² + 3x + 8 = 0
x₁ = ![\frac{-3-\sqrt{33} }{2} \frac{-3-\sqrt{33} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3-%5Csqrt%7B33%7D%20%7D%7B2%7D)
x₂ = ![\frac{-3+\sqrt{33} }{2} \frac{-3+\sqrt{33} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%2B%5Csqrt%7B33%7D%20%7D%7B2%7D)